Amount and distribution of benthic marine litter along Sardinian fishing grounds (CW Mediterranean Sea). (May 2018) - Alvito, Andrea; Bellodi, Andrea; Cau, Alessandro; Moccia, Davide; Mulas, Antonello; Palmas, Francesco; Pesci, Paola; Follesa, Maria Cristina
Highlights: 302 hauls have been performed by mean of trawl nets. Plastic resulted the main category for frequency of occurrence, weight and abundance. Investigated area resulted less impacted than other Mediterranean areas. Fishermen behaviour emphasized a lack of interest for marine debris pollution. Abstract: Reports of marine litter pollution first appeared in scientific literature of the early 1970s; yet, more than 40 years later, no rigorous estimates exist of the amount of litter existing in the marine environment. To cope with this global urgency, this study reports the status of marine litter abundance along fishing grounds surrounding the island of Sardinia (CW Mediterranean Sea; FAO Geographical Sub-Area 11) through three years of trawl surveys. A total of 302 hauls, covering a total of 18.4 km 2 of trawled surface were carried out in the framework of the MEDITS campaign, at depths comprised between 0 and 800 m. A total of 918 items were collected and sorted, with the highest concentration observed above 200 m depth. Overall, plastic was the dominant component of litter, followed by glass and metal. Comparing our results with other areas from the Mediterranean basin, Sardinian waters showed a lower impact, possibly as a consequence of multiple factors such as the lower human population density and the low flow of the main rivers, among others. In addition, fishermen behaviour with respect to marine litter was investigated by mean of anonymous questionnaires, emphasizing the necessity to further develop management policies and infrastructures supporting litter disposal.